To get vaccinated or not? An investigation of the relationship of linguistic assignment of agency and the intention to obtain the COVID-19 vaccine. Issue 5 (20th October 2022) - Anthony, Kathryn E.; Bagley, Braden; Petrun Sayers, Elizabeth L.; Forbes Bright, Candace
ABSTRACT: Just nine months after the World Health Organization declared the outbreak of SARS-CoV-2 a global pandemic, the Food and Drug Administration granted emergency use authorization (EUA) for the Pfizer-BioNtech and Moderna vaccines in December 2020, followed by EUA for the Johnson & Johnson vaccine in February 2021. Although achieving herd immunity through vaccinations is the greatest hope for ending the pandemic, the COVID-19 vaccination effort has been plagued by misinformation and mistrust. Given the urgency to vaccinate the population, public health officials must construct messages that encourage individuals to obtain the COVID-19 vaccine. The current study examines the impact of linguistic assignment of agency on an individual's desire to get vaccinated. Guided by the EPPM, participants (N= 296) were randomly assigned to receive either a virus agentic message or a human agentic message. The researchers discovered that the virus agentic message resulted in a greater intention to obtain the vaccine. Further, participants who received the virus agentic message reported a stronger sense of perceived self-efficacy and perceived susceptibility. Additionally, participants who perceived the societal reaction to the pandemic to be appropriate, as well as those who knew at least one person who had died from the virus, were more likely to express an intention to get vaccinated.